Effect of partial magnetic field on thermo gravitational convection in an inclined cavity. Issue 1 (February 2021) - Chatterjee, Deep; Manna, Nirmal K.; Mandal, Dipak Kumar; Biswas, Nirmalendu
Abstract: The study presented gives a succinct overview of the effect of partially applied magnetic field on natural convective heat transfer in a differentially heated inclined cavity. The left and right sidewalls are differentially heated such that their temperatures are maintained (at T h and T c respectively), while the top and bottom walls have been assumed to be adiabatic, such that heat transfer through those walls can be neglected. The results are supposed to elucidate the effect of changing Rayleigh number (Ra), Hartmann number (Ha), and cavity inclination angle (f ) on the thermo-fluid phenomena. The analysis is carried out numerically utilizing finite volume based computing code. The results have been demonstrated in the form of streamlines, isotherms, and average Nusselt number. From the analysis, it is found that the flow structure and associated heat transfer characteristics are severely influenced by the studied range of governing parameters.